2007
DOI: 10.1007/s00426-007-0125-3
|View full text |Cite
|
Sign up to set email alerts
|

Self produced and observed actions influence emotion: the roles of action fluency and eye gaze

Abstract: Affective responses to objects can be influenced by cognitive processes such as perceptual fluency. Here we investigated whether the quality of motor interaction with an object influences affective response to the object. Participants grasped and moved objects using either a fluent action or a non-fluent action (avoiding an obstacle). Liking ratings were higher for objects in the fluent condition. Two further studies investigated whether the fluency of another person's actions influences affective response. Ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 45 publications
4
45
1
Order By: Relevance
“…A number of studies demonstrate that people tend to like stimuli more that are easy to understand (e. g., Jacoby and Dallas, 1981; Whittlesea, 1993). Researchers have also demonstrated that we like objects more that we have watched others interact with smoothly and efficiently, compared to objects that were interacted with awkwardly (Hayes et al, 2008), thus demonstrating a link between liking and perceived action fluidity. In the present study, we add another element to the relationship between liking and action perception: namely, that observers also tend to rate actions that are beyond their physical abilities as more likeable.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies demonstrate that people tend to like stimuli more that are easy to understand (e. g., Jacoby and Dallas, 1981; Whittlesea, 1993). Researchers have also demonstrated that we like objects more that we have watched others interact with smoothly and efficiently, compared to objects that were interacted with awkwardly (Hayes et al, 2008), thus demonstrating a link between liking and perceived action fluidity. In the present study, we add another element to the relationship between liking and action perception: namely, that observers also tend to rate actions that are beyond their physical abilities as more likeable.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the more fluently a perceiver can process a stimulus, the more positive their aesthetic response becomes. This idea has received support from research showing that observing or performing smooth reach and grasping movements toward everyday objects results in higher aesthetic ratings of those objects compared to objects that were grasped in a more awkward way (Hayes et al, 2008). In a recent paper, Montero suggested that dance training can facilitate the perception of certain aesthetic qualities of a dance, meaning that aspects such as grace, power, and precision may go unnoticed without any physical practice (Montero, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Our first hypothesis is that the user's affective appraisal of the VE depends on the playing view. This hypothesis is based on the previous finding that affective ratings for objects depend on viewing perspective (Hayes et al, 2006(Hayes et al, , 2008. Our second hypothesis is that a 1PP generates more engagement, because this perspective is known to yield a higher sense of spatial presence and more cognitive involvement (Kallinen et al, 2007).…”
Section: Aim Of the Experimentsmentioning
confidence: 97%